Service Learning in Agronomy: Actions and Reflection in a Course Conducted in Rural Communities in Costa Rica - Mazzola, Julieta (2024)
Objective. This article examines the Agronomy major course Community Scenario (Work Experience Course), considering the fundamental elements of the service-learning strategy. It also analyzes the primary learnings that students value during their community experience. Methodology. This qualitative study adopts a descriptive case study approach that examines the course under the service-learning model. It analyzes the integration of the course into the university curriculum, the organization, the promotion of civic responsibility, fieldwork to meet community needs, and reflection activities (United States Congress, 1990). To address the learnings valued by the students, the documentary observation technique was used. A reflection tool was employed to collect the learnings identified by a group of 38 students. The learnings were subsequently analyzed with a focus on three domains: cognitive, behavioral, and affective (Knight-McKenna et al., 2018). Findings and conclusions. The community scenario reveals the presence of the key components of service learning. It exhibits certain strengths in terms of academic organization and reflection and areas with potential for improvement. The participating students value learnings in the affective domain, followed by the behavioral domain, and finally the cognitive domain. Noteworthy learnings include technical knowledge, interpersonal relationships, and knowledge of social conditions and context. Recommendations: It is recommended to continue studying the impact of this course and other community-based courses on student learning.